2016
DOI: 10.1111/pce.12775
|View full text |Cite
|
Sign up to set email alerts
|

How specialized volatiles respond to chronic and short‐term physiological and shock heat stress in Brassica nigra

Abstract: Brassicales released volatile glucosinolate breakdown products upon tissue mechanical damage, but it is unclear how glucosinolate volatile release responds to abiotic stresses such as heat stress. We used three different heat treatments called as mild -and long-term stress and shock-heating to gain insight into stress-dependent changes in volatile blends and photosynthetic characteristics in Brassica nigra (L.) Koch. The reduction in net assimilation rate (A) in temperature response curve measurements was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 128 publications
(153 reference statements)
7
55
0
Order By: Relevance
“…These quantitative relationships are in agreement with former studies demonstrating stress severity-dependent release of LOX compounds and methanol for a variety of stresses including ozone [46,47,83], heat [40,84], mechanical wounding [30], insect herbivory [35,36,62]. In a previous study, we have demonstrated analogous MeJA concentration-dependent LOX and methanol emission responses [39].…”
Section: Meja Concentration-dependent Emissions Of Lox and Methanolsupporting
confidence: 92%
“…These quantitative relationships are in agreement with former studies demonstrating stress severity-dependent release of LOX compounds and methanol for a variety of stresses including ozone [46,47,83], heat [40,84], mechanical wounding [30], insect herbivory [35,36,62]. In a previous study, we have demonstrated analogous MeJA concentration-dependent LOX and methanol emission responses [39].…”
Section: Meja Concentration-dependent Emissions Of Lox and Methanolsupporting
confidence: 92%
“…Whereas several studies demonstrated the effects of heat on isoprene emission ( Sharkey et al., 2008 ; Pollastri et al., 2014 ; Niinemets and Sun, 2015 ; Bamberger et al., 2017 ), less information is available on the dynamic response of other VOC fluxes toward prolonged heat stress ( Fares et al., 2011 ; Kleist et al., 2012 ; Kask et al., 2016 ). H. halimifolium is not a strong isoprene emitter ( Yáñez-Serrano et al., 2018 ), similar to what has been reported for other members of the Cistaceae family ( Kesselmeier and Staudt, 1999 ; Bracho-Nunez et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a different effect of the AM fungal species was again evident, with R. intraradices -inoculated plants that showed similar level of all targeted metabolites in comparison with NS plants, suggesting an enhanced tolerance to this type of stress promoted by this AM fungal species. In tomato, a vast array of VOCs was found to be emitted under biotic ( Digilio et al, 2010 ) and abiotic stresses, including water deficit ( Catola et al, 2018 ), flooding ( Copolovici and Niinemets, 2010 ), cold and heat ( Copolovici et al, 2012 ; Kask et al, 2016 ). In our experimental study, where necessarily a MS has been used to permit the combined test with aphids, the emission of a typical tomato VOC bouquet under NS and water deficit conditions was determined.…”
Section: Discussionmentioning
confidence: 99%